Application of amplified ribosomal DNA restriction analysis in identification of Acinetobacter baumannii from a tertiary teaching hospital, Malaysia - Kong, B.H.; Hanifah, Y.A.; Yusof, M.Y.; Thong, Kwai Lin (Malaysian Society for Parasitology, 2011)
Acinetobacter baumannii, genomic species 3 and 13TU are being increasingly reported as the most important Acinetobacter species that cause infections in hospitalized patients. These Acinetobacter species are grouped in the Acinetobacter calcoaceticus- Acinetobacter baumannii (Acb) complex. Differentiation of the species in the Acb-complex is limited by phenotypic methods. Therefore, in this study, amplified ribosomal DNA restriction analysis (ARDRA) was applied to confirm the identity A. baumannii strains as well as to differentiate between the subspecies. One hundred and eighty-five strains from Intensive Care Unit, Universiti Malaya Medical Center (UMMC) were successfully identified as A. baumannii by ARDRA. Acinetobacter genomic species 13TU and 15TU were identified in 3 and 1 strains, respectively. ARDRA provides an accurate, rapid and definitive approach towards the identification of the species level in the genus Acinetobacter. This paper reports the first application ARDRA in genospecies identification of Acinetobacter in Malaysia